Evaluating community health worker education policy through a National Certificate (Vocational) Primary Health qualification lens - Michelle N.S. Janse van Rensburg; Tessa S. Marcus (AOSIS, 2020)
Background: In 2018, the South African National Department of Health (NDoH) published a 5-year policy framework and strategy for Ward-Based Primary Healthcare Outreach teams to improve team management and leadership and support service delivery. In the same year, the World Health Organization (WHO) published guidelines on health policy and system support to optimise Community Health Worker (CHW) programmes. Aim: This article aims to assess the National Certificate (Vocational), or NC(V), Primary Health qualification in terms of the education and training guidelines and recommendations of the 2018 NDoH and WHO policy documents. Setting: The qualification was initiated in 2013 at 12 Technical and Vocational Education and Training (TVET) colleges across South Africa. The evaluation covered the period 2013-2017. Methods: Pragmatic qualitative enquiry was used to examine the context, design, implementation and outcomes of the qualification. Data collection involved document reviews, key informant in-depth interviews and focused group discussions, and individual reflections with respondents from one part-time and two full-time offerings at two colleges. Analyses of emergent themes were interpreted using appropriate models and theoretical frameworks. Results: The Department of Higher Education and Training (DHET) created and implemented a standardised, curriculated national programme for CHW education that structured theoretical and practical learning over time to ensure assimilation of content and its application in practice. Conclusion: NC(V) Primary Health, as a single, national, quality-assured qualification for CHWs, meets WHO 2018 guidelines and recommendations, NDoH training needs and CHWs learning expectations, especially when offered part-time. Despite the termination of the programme, it remains a relevant option for CHWs in South Africa and elsewhere.